Application of Gaseous ClO2 on Disinfection and Air Pollution Control: A Mini Review - Tse-Lun Chen; Yi-Hung Chen; Yu-Lin Zhao; Pen-Chi Chiang (Aerosol and Air Quality Research)
Abstract During the sever pandemic of coronavirus, the development and deployment of efficient disinfection technology have attracted hospitals’ attention. Chlorine dioxide (ClO2) gas has been validated as an efficient disinfector and air pollution control due its high oxidation ability. This article reviewed the principles and application of ClO2 gas on disinfection, sterilization and air pollutants abatement. The principles of ClO2 gas production, chemistry and related generator issues were discussed. We also review some case studies of the application of ClO2 gas in the medical field and food industry as a sterilizer. Oxidation of nitrogen oxide (NOx), sulfur oxide (SOx), mercury (Hg), and volatile organic compounds (VOCs) using ClO2 gas has been investigated. The process chemistry and demonstration of applying ClO2 gas for air pollutants oxidation and absorption have also been provided. In conclusion, we suggest the future priority research direction of ClO2 gas application are included the development of smart and robust ClO2 gas release system, the integration of an innovative robotic technology in ClO2 sterilization for epidemic prevention, and the evaluation of ClO2 emissions impact on indoor air quality in hospitals.